The burden of cancers associated with HIV in the South African public health sector, 2004–2014: a record linkage study - Dhokotera, Tafadzwa; Bohlius, Julia; Spoerr, Adrian; Egger, Matthias; Ncayiyana, Jabulani; Olago, Victor; Singh, Elvira; Sengayi, Mazvita (My University, 2019)
Introduction: The impact of South Africa’s high human immunodeficiency virus (HIV) burden on cancer risk is not fully understood, particularly in the context of antiretroviral treatment (ART) availability. We examined national cancer trends and excess cancer risk in people living with HIV (PLHIV) compared to those who are HIV-negative. Methods: We used probabilistic record linkage to match cancer records provided by the National Cancer Registry to HIV data provided by the National Health Laboratory Service (NHLS). We also used text search of specific HIV terms from the clinical section of pathology reports to determine HIV status of cancer patients. We used logistic and Joinpoint regression models to evaluate the risk and trends in cancers in PLHIV compared to HIV-negative patients from 2004 to 2014. In sensitivity analysis, we used inverse probability weighting (IPW) to correct for possible selection bias. Results: A total of 329,208 cancer cases from public sector laboratories were reported to the NCR from 2004 to 2014 with the HIV status known for 95,279 (28.9%) cancer cases. About 50% of all the female cancer cases (n = 30,486) with a known status were HIV-positive. PLHIV were at higher risk of AIDS-defining cancers (Kaposi sarcoma [adjusted OR:134, 95% CI:111–162], non-Hodgkin lymphoma [adjusted OR:2.73, 95% CI:2.56–2.91] and, cervix [adjusted OR:1.70, 95% CI:1.63–1.77], conjunctival cancer [adjusted OR:21.5, 95% CI:16.3–28.4] and human papilloma virus (HPV) related cancers (including; penis [adjusted OR:2.35, 95% CI:1.85–2.99], and vulva [adjusted OR:1.94, 95% CI:1.67–2.25]) compared to HIV-negative patients. Analysis using the IPW population yielded comparable results. Conclusion: There is need for improved awareness and screening of conjunctival cancer and HPV-associated cancers at HIV care centres. Further research and discussion is warranted on inclusive HPV vaccination in PLHIV.
Keywords: HIV and cancer; Epidemiology; South Africa; Antiretroviral era; Cancer risk; SDG-3: Good health and well-being; SDG-16: Peace, justice and strong institutions